2015
DOI: 10.1002/ijc.29574
|View full text |Cite
|
Sign up to set email alerts
|

Nsc23925 prevents the development of paclitaxel resistance by inhibiting the introduction of P‐glycoprotein and enhancing apoptosis

Abstract: Strategies to prevent the emergence of drug resistance will increase the effectiveness of chemotherapy treatment and prolong survival of women with ovarian cancer. The aim of the current study is to determine the effects of NSC23925 on preventing the development of paclitaxel resistance in ovarian cancer both in cultured cells in vitro and in mouse xenograft models in vivo, and to further elucidate these underlying mechanisms. We first developed a paclitaxel-resistant ovarian cancer cell line, and demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 46 publications
(135 reference statements)
0
28
0
Order By: Relevance
“…The identification and development of specific and potent inhibitors of PGP1 for clinical use in combination with conventional chemotherapy appears to be a promising area in the field of novel anticancer therapeutics in reversing drug resistance (Duan et al, ; Ferry et al, ; Luetke et al, ; Yang et al, ). In this study, we identified NVP‐TAE684 as one of the most effective MDR reversing agents, after screening 500+ compounds from a pre‐selected, kinase‐directed small molecule library.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification and development of specific and potent inhibitors of PGP1 for clinical use in combination with conventional chemotherapy appears to be a promising area in the field of novel anticancer therapeutics in reversing drug resistance (Duan et al, ; Ferry et al, ; Luetke et al, ; Yang et al, ). In this study, we identified NVP‐TAE684 as one of the most effective MDR reversing agents, after screening 500+ compounds from a pre‐selected, kinase‐directed small molecule library.…”
Section: Discussionmentioning
confidence: 99%
“…The mouse monoclonal antibody to human actin was purchased from Sigma‐Aldrich. Western blot analysis was performed as previously described (Yang et al, ). The levels of expressed proteins were visualized by scanning the membrane on an Odyssey Infrared Imaging System (LI‐COR Biosciences, Lincoln, NE, USA) with both 680 and 800 nm channels.…”
Section: Methodsmentioning
confidence: 99%
“…The distribution of the Si and N pDOS resembles that of other nitridosilicates composed of [SiN 4 ] tetrahedra. In β-Si 3 N 4 , which is composed only of [SiN 4 ] tetrahedra and has similar Si-N distances, the VB spectral weight is similarly distributed in two spectral ranges with similar widths and separations [58,59]. In MSiN 2 nitridosilicates with larger cations (M = Sr, Ba) the Si and N spectral weight is similar in shape, but the width of the valence bands are broadened [15].…”
Section: Dft Calculation Detailsmentioning
confidence: 99%
“…The clinical significance of P-gp and MRP1 in drug resistance is supported by evidence that their expression indicates an adverse prognosis in patients with a range of types of cancer (11,12). Yang et al (13) demonstrated that Nsc23925 could prevent the development of paclitaxel resistance by inhibiting the expression of P-gp and enhancing apoptosis. Therefore, it was concluded from the data of the present study that 5-Aza-CdR enhances MMC chemosensitivity of T24 cells by suppressing P-gp and MRP1 expression.…”
Section: Discussionmentioning
confidence: 99%